Factors Influencing the Control of Diabetes Measured via Glycated Hemoglobin Concentrations in Adults with Type 1 Diabetes - Beata I. Sińska; Ewa Rzońca; Alicja Kucharska; Robert Gałązkowski; Iwona Traczyk; Patryk Rzońca (MDPI AG, 2023)
Numerous complications of type 1 diabetes (T1D) may be prevented through suitable glycemic control. Glycated hemoglobin (HbA1c) may be one of the markers for the early detection of the metabolic imbalance characteristic of the disease. However, optimal control of diabetes is not achieved in a large group of patients. It was demonstrated that numerous factors (sociodemographic, psychological, and clinical) contributed to this condition. The aim of the study was to identify factors influencing the control of diabetes measured via glycated hemoglobin concentrations in people with T1D. Independent factors influencing better diabetes control measured via HbA1c in the study group included higher disease acceptance, higher nutritional adherence, lower BMI, and a lower risk of eating disorders. Describing the determinants will allow for the improvement of the system of care provided to people with T1D and for it to comprise important psychological variables related to self-care and acceptance of the disease.